낙상에 의해 상악 전치부에 외상을 입은 노인 환자에서 수술을 배제하고 고정성 보철물을 이용하여 수복한 증례 - 배윤주; 최순영; Bae, Yoonjoo; Choi, Sunyoung (Taehan Chikwa Poch'ol Hakhoe chi, 2019)
Fall is the most common cause of trauma in the elderly and a major reason of dental injury. Maxillary anterior region is the most vulnerable area to the traumatic fall. Loss of teeth and adjacent tissue in this area results in maxillofacial defects and inappropriate maxillomandibular relationship. Reconstruction of the loss requires comprehensive and careful planning to fulfill not only functional but also esthetic demand. Prosthetic approach can avoid surgically extensive intervention, reducing both treatment cost and time. This clinical report describes a 78-year-old woman with the loss of teeth and alveolar bone in maxillary anterior region due to a traumatic fall, rehabilitated with a metal-ceramic fixed dental prosthesis using gingival porcelain. 낙상에 의해 치아 및 주변 조직이 손상되어 구강 내 경조직 및 연조직의 상실이 발생한 경우 이를 재건하기 위한 방법으로 외과적 접근법과 보철적 접근법이 제시될 수 있다. 치은부가 포함된 보철물을 이용하는 보철적 접근법은 외과적 수술을 생략함으로써 치료 과정을 단순화 하고 치료 시간과 비용을 줄일 수 있다는 장점이 있다. 특히, 상악 전치부 치아 및 치조골의 상실을 보철적으로 재건하는 경우 치은부가 포함된 보철물에 의해 확실한 안면부 지지를 제공하게 되어 안모의 심미적 결손을 보상할 수 있고 상 하악의 관계를 개선시킬 수 있다. 본 증례는 낙상으로 인해 상악 전치부에 광범위한 손상을 입은 노인 환자에서 수술을 배제하고, 치은 색상의 도재가 포함된 고정성 보철물을 이용하여 수복함으로써 예지성 있는 심미적 결과를 얻었기에 이를 보고하고자 한다.